Answer:
The equation y = (2/3)x - 1 describes the linear function.
Explanation:
We know for a line y = mx + c, m stands for gradient or the slope of line.
C stands for y- intercept by the line.
When we analyse the graph y- intercept is (-1)
So c = -1
and this line passes through two points (3, 1) and (6, 3)
Therefore the slope this line =
![((y-y'))/((x-x'))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/pqkfv8j6ukdzrcs9fedb7fl1esz4cvg9re.png)
m =
![m=(3-1)/(6-3)=(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8dp3igw4uqpznl9rdr7o5qnw9u2lofb248.png)
So by putting these values in the equation we can get the original equation.
![y=(2)/(3)x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sne34319j5zrpatfhfjf60j62k57yhu5hl.png)